Conquering new frontiers in research on store atmospheres: Kinetic and synesthetic qualities - Christian Julmi (Ambiances)
The study of store atmospheres and their effects on the consumer’s behaviour has become a significant area of research within marketing. In this context, the aim of this article is twofold. First, it is shown that the widely accepted S-O-R model is incommensurable with the store atmosphere as the object of investigation. Second, the concept of bridging qualities from German philosopher Hermann Schmitz is introduced as a promising alternative to the study of store atmospheres avoiding the identified incommensurability. As the concepts of Schmitz have not been considered within marketing theory yet, the article breaks new ground.